Biofertilizer for control of Guignardia citricarpa, the causal agent of citrus black spot - Kupper, K. C.; Bettiol, W.; de Goes, A.; de Souza, P. S.; Bellotte, JAM (Elsevier B.V., 2006)
Biofertilizers generated from the anaerobic and aerobic digestion of cattle manure, known as Bio1 and Bio2, respectively, were studied with regard to their microbial composition and effect on the mycelial growth of Phyllosticta citricarpa, the causal agent of citrus black spot (CBS). Two field experiments were conducted to determine the biofertilizer's potential (Bio1) in controlling CBS (2001/2002 and 2002/2003 crops). It was observed that the greatest number of microorganisms was found in the aerobically produced biofertilizer. Bio2 did not inhibit the mycelial growth of P. citricarpa. Mycelial growth of P. citricarpa was inversely proportional to the Bio1 biofertilizer concentration. In the 2001/2002 cropping season, the Biol effect in controlling CBS was directly proportional to its concentration, at the rate of 0 (healthy fruit), with R-2 = 0.88. Biol had a significant effect in controlling CBS, at a concentration of 10%, during the 2001/2002 cropping season, with DI values of 0.246 and 0.229 for the. 10 and 20% doses, respectively, compared to DI of 0.329 for the control. A directly proportional effect of the biofertilizer concentration on the percentage of fruits with a rating of zero was. also observed in the 2002/2003 cropping season, with R-2 = 0.48. However, even at doses higher than in the preceding cropping season, the biofertilizer was less effective, possibly due to a higher occurrence of the disease. Copper oxychloride and combined applications of copper oxychloride and carbendazim plus mancozeb controlled the disease. The possibility of using the biofertilizer as a protective biofungicide to replace copper oxychloride, especially in organic agriculture, should be explored. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: organic matter; alternative control; Biological control; Phyllosticta citricarpa; Guignardia citricarpa; cattle manure